2022
DOI: 10.3389/fimmu.2022.912069
|View full text |Cite
|
Sign up to set email alerts
|

POP1 inhibits MSU-induced inflammasome activation and ameliorates gout

Abstract: Canonical inflammasomes are innate immune protein scaffolds that enable the activation of inflammatory caspase-1, and subsequently the processing and release of interleukin (IL)-1β, IL-18, and danger signals, as well as the induction of pyroptotic cell death. Inflammasome assembly and activation occurs in response to sensing of infectious, sterile and self-derived molecular patterns by cytosolic pattern recognition receptors, including the Nod-like receptor NLRP3. While these responses are essential for host d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 57 publications
(106 reference statements)
0
15
0
Order By: Relevance
“… 23 - 26 Thereby, POPs interfere with the polymerization of inflammasome components and consequently prevent inflammasome assembly and inflammation in vivo . 23 , 27 - 30 A comparable competitive binding mechanism has been proposed for the three human COPs, CARD16/Cop/Pseudo-ICE, CARD17/Inca, and CARD18/Iceberg, but targeting the CARD in caspase-1 or ASC instead of the PYD. 31 - 34 However, most of these studies have been performed by overexpression in epithelial cells before the discovery of the inflammasome, and consequently any relevance of COPs in regulating inflammasome responses and inflammatory disease in vivo remains unknown.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“… 23 - 26 Thereby, POPs interfere with the polymerization of inflammasome components and consequently prevent inflammasome assembly and inflammation in vivo . 23 , 27 - 30 A comparable competitive binding mechanism has been proposed for the three human COPs, CARD16/Cop/Pseudo-ICE, CARD17/Inca, and CARD18/Iceberg, but targeting the CARD in caspase-1 or ASC instead of the PYD. 31 - 34 However, most of these studies have been performed by overexpression in epithelial cells before the discovery of the inflammasome, and consequently any relevance of COPs in regulating inflammasome responses and inflammatory disease in vivo remains unknown.…”
Section: Introductionmentioning
confidence: 83%
“… 20 , 21 , 87 We previously demonstrated that this first step of nucleated ASC polymerization is regulated by POP family members by competitive binding to the PYD of either ASC or upstream sensors, there by ameliorating inflammatory disease. 23 , 27 , 29 , 30 Reminiscent of the three POP family members, the three COPs also evolved in higher primates. 36 , 89 However, their precise role is less well described, largely due to inconclusive and inconsistent studies, including CARD18 inhibiting IL-1β release in one but not another study, 34 , 87 studies of non-immune cells, 31 - 33 , 86 or studies of primed but not inflammasome-activated macrophages before the discovery of the inflammasome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since ASC is the central hub in inflammasome signaling, its function is tightly controlled, including in the sensor level ( 232 ), and also in its interactions with other ASC molecules and the sensor/caspase-1 by alternative splicing ( 233 235 ), post-translational modifications ( 236 241 ), PYD-only proteins ( 242 244 ), and CARD-only proteins ( 245 247 ). ASC oligomerization and speck formation can be disrupted by gene mutation ( 248 , 249 ), pathogens ( 250 ), bioactive extracts ( 251 254 )/derivatives ( 255 257 )/metabolites ( 258 ), cytokines ( 259 ), complements ( 260 ), or chemicals ( 261 263 ) or further stabilized by L-plastin ( 264 ), inhibiting or facilitating downstream signaling, respectively.…”
Section: Events Upstream Of Pyroptosis and Cytokine Secretion In Infl...mentioning
confidence: 99%